(untitled) (Research, Society and Development, 2022)
The malocclusions are a public health problem and have a multifactorial character. To reduce its incidence, knowledge about the profile of patients and the possible causal factors of the manifestation of these dysfunctions is necessary. The objective of the research was to trace the epidemiological profile and evaluate the prevalence of malocclusion in patients aged 6 to 16 years treated in the Children’s Clinic II discipline at the Clínica Escola da Odontologia of the Federal University of Campina Grande in the city of Patos-Paraíba. The sample consisted of 161 medical records and the data encompassed the following axes: demographic variables, dental history, hygiene, food and possible harmful habits and their occlusion tests. Thus, it was found that 58% of the sample was female and that 93% of the patients had already had their first dental appointment. As for harmful habits, 129 individuals had some harmful habit, with nail biting being the most mentioned and finger sucking the most associated with the development of malocclusions. Regarding the orthodontic diagnosis, it was found that the most frequent alterations were crossbite and open bite, where the Angle class 1 pattern was predominant, followed by the class 2 pattern and, finally, the class 3 pattern. the importance of dental follow-up is reinforced since the eruption of the first teeth, as well as the knowledge of the profile of the patients treated and the problems of greater incidence, in order to provide a foundation for intervention planning.